DESKRIPSI PEMAKAIAN BAHASA DALAM KORAN BUTON POS EDISI SELASA, 20 MEI 2016 - Suryanti Suryanti (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
Abstract: Description Language Usage in Buton Post newspaper edition Tuesday, May 20, 2016. The expected goal with this study was to determine the description of language use in the postal Buton newspaper. The method used to pengunpulan data in this research is descriptive qualitative method because the purpose of this study was to decrypt the use of the language contained in Buton post. The data were analyzed using qualitative approach for the presentation of data in a sentence or words in the form of a narrative or descriptive. The research results indicate that the use of the language contained in the paper Buton Post edition Tuesday May 20, 2016 contains elements of grammar that is writing the correct word, contains elements of grammatical, which uses basic words and affixes like the words contained in the newspaper Buton Post Edition Tuesday , May 20, 2016.